The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1016/j.ultras.2014.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic wave propagation in concentrated slurries – The modelling problem

Abstract: The suspended particle size distribution in slurries can, in principle, be estimated from measured ultrasonic wave attenuation across a frequency band in the 10s of MHz range. The procedure requires a computational model of wave propagation which incorporates scattering phenomena. These models fail at high particle concentrations due to hydrodynamic effects which they do not incorporate. This work seeks an effective viscosity and density for the medium surrounding the particles, which would enable the scatteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…However, when particles are close together, at high concentrations, or high number density, the thermal and shear modes scattered by one particle may have significant amplitude when they reach the surface of a neighbouring particle. [15][16][17] They can then be re-scattered by that particle, and contribute to the scattered compressional wave. This kind of mode-conversion is also generated partially as a result of the difference in acoustic impedance between the scatterer and the surrounding medium.…”
Section: Introductionmentioning
confidence: 99%
“…However, when particles are close together, at high concentrations, or high number density, the thermal and shear modes scattered by one particle may have significant amplitude when they reach the surface of a neighbouring particle. [15][16][17] They can then be re-scattered by that particle, and contribute to the scattered compressional wave. This kind of mode-conversion is also generated partially as a result of the difference in acoustic impedance between the scatterer and the surrounding medium.…”
Section: Introductionmentioning
confidence: 99%
“…The variations of component concentrations have effects on the physical properties of multicomponent mixtures, including density, viscosity and bulk modulus [ 9 ]. So the ultrasonic waves (amplitude and shape) transmitted through the multicomponent mixtures will also change along with the component concentrations, and, in turn, it is possible to measure the component concentrations through analyzing the ultrasonic signals.…”
Section: Introductionmentioning
confidence: 99%
“…However, existing scattering models have been demonstrated to be limited in the range of concentration and particle size to which they can be applied; high concentrations or small particles cause inaccuracies in the models. [9][10][11][12][13][14] For an aqueous suspension the maximum concentration for traditional models is around 15%v/v for 1 micron diameter particles at 5 MHz.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental data in both suspensions and emulsions have demonstrated that the standard multiple scattering model does not correctly predict the attenuation spectrum for small particles, low frequencies, and at high concentrations. [9][10][11][12][13][14] The neglect of the multi-mode scattering contribution is believed to be the reason, and thus causes a significant constraint on the use of ultrasonics as a process analytical technology.…”
Section: Introductionmentioning
confidence: 99%